Rate of absorption and optimal amount of the hydrogel products depending on the pH of different water sources - Djonibekova Nafosat Ergash kizi (Caspian Journal of Environmental Sciences)
In this article, the process of absorption of various hydrogels and their optimal concentration in distilled, stream, underground (drainage) water at pH 5, 7 and 9 were determined. AQUASORB from France, STOCKOSORB from Germany, Mujiza hydrogel from Uzbekistan were used in the experiment. According to the results, 12.5 g AQUASORB, 15 g  STOCKOSORB, and 60 g Mujiza were used in 1 L distilled water with a medium pH of 5 and a gel of 100% volume was formed. When the pH of the distilled water was 7, 15 g AQUASORB, 20 g STOCKOSORB, and 50 g Mujiza  were used. Distilled water was alkaline, when pH was 9 and 10 g AQUASORB, 7.5 g STOCKOSORB, and 40 g Mujiza were used. It was determined that the hydrogels' sorption amount was in different concentrations even when the water of the stream and well (drainage) were pH 5, 7 and  9, and a recommendation was given for its use.